THEORETICAL FOUNDATIONS OF THE STUDY OF TOURISM AS AN OBJECT OF PUBLIC ADMINISTRATION - Krutii А. M. (Pressing Problems of Public Administration, 2021)
Tourism is developing dynamically under the influence of the spread of travel and the activities of social and public institutions. This takes place in conditions of active interaction and dialogue between representatives of public authorities, business and the public. It is important for modern Ukraine to determine the ways of formation and implementation of state policy in the field of tourism and the possibility of participation of the traveler. Active human participation, demand for social and spiritual needs, new knowledge and innovative tourism practices, participation in state-building processes, are the basis for the success of public administration in the tourism sector. However, the theoretical foundations of the study of tourism as an object of public administration in the scientific literature is not sufficiently presented. The source analysis highlights the separation of four block clusters of scientific approaches: public administration, socio-economic, political and legal, socio-cultural. Within the framework of the public administration approach, the development of tourism is considered in the context of structural and functional improvement of public administration institutions and personnel policy. Research of professionalism and personal-professional qualities of a person is an important factor of professional activity in the field of tourism. According to the authors of the public administration approach, it should be emphasized that most of them see the need to consider tourism policy as a system of measures implemented by parliaments, governments, public and private organizations responsible for tourism. Some studies see the state’s tourism policy as necessary to plan the development of the tourism market players themselves. Thus, the analysis of theoretical foundations in the field of tourism as an object of public policy covers a wide range of mechanisms, institutions, tools, methods and technologies of public administration, political and legal, socio-economic and socio-cultural nature, which further develops other value components social processes in which tourism develops as a social phenomenon and the organizing and coordinating influence of the state at all management levels on the peculiarities of its development.